2020
DOI: 10.24326/asphc.2020.4.10
|View full text |Cite
|
Sign up to set email alerts
|

BIOLOGICAL VALUE AND ESSENTIAL OIL COMPOSITION OF TWO Monarda SPECIES FLOWERS

Abstract: In this study the quantity of the main nutritional and bioactive compounds, as well as the antioxidant activity (DPPH, FRAP and ABTS methods) and essential oil composition of Monarda fistulosa L. and Monarda citriodora subsp. austromontana Cerv. ex Lag. ‘Bees’ Favourite’ flowers were investigated. The field experiment was carried out for three years (2014–2016) and the laboratory analyses in the years 2015–2016. The obtained results showed that M. citriodora flowers were characterized by a dry matter (22.42%),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 0 publications
1
18
0
8
Order By: Relevance
“…As Mazza and Marshall indicated, the chemical composition of M. fistulosa essential oils is dependent on genotype and geographic origin [64]. Indeed, our results were comparable to the composition of M. fistulosa essential oils obtained from the Szczecin region in Poland, which had carvacrol, p-cymene, α-terpinene, and γ-terpinene as the major constituents [62] and were distinct from the high thymol content (60.8%) in M. fistulosa essential oils reported by Lawrence [65].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…As Mazza and Marshall indicated, the chemical composition of M. fistulosa essential oils is dependent on genotype and geographic origin [64]. Indeed, our results were comparable to the composition of M. fistulosa essential oils obtained from the Szczecin region in Poland, which had carvacrol, p-cymene, α-terpinene, and γ-terpinene as the major constituents [62] and were distinct from the high thymol content (60.8%) in M. fistulosa essential oils reported by Lawrence [65].…”
Section: Discussionsupporting
confidence: 85%
“…The genus Monarda is represented by 20 native species, with M. fistulosa (wild bergamot) essential oils being used medicinally to treat cardiovascular defects, wounds, colds and flu, gastrointestinal disorders, insomnia, and infant convulsions [1]. Along with potent antimicrobial and antioxidant activity [16,62], Duke suggested that M. fistulosa also has anticarcinogenic properties [63]. In the present study, we defined the chemical profile of essential oils extracted from M. fistulosa flowers (MEO Fl ) and leaves (MEO Lv ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, methyl carvacrol is also found to constitute about 4.80% to 4.89% of the Eos (Markovska et al, 2020). However, the composition of active compounds depends on the genotype and the cultivation place (Grzeszczuk et al, 2020).…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…In order to obtain information regarding the antioxidant activities of thymol and carvacrol, several tests can be conducted. The first one is the DPPH test which will monitor the effectiveness of the compounds against free radicals (Grzeszczuk et al, 2020). According to the study by Yildiz et al (2020), thymol shows 25.0% of DPPH antiradical activity and carvacrol shows 18.3% activity at 1000 ppm concentration.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%
“…Además, las flores son ricas en néctar y polen, y diferentes estudios han demostrado que el polen es rico en vitaminas y minerales (Grzeszczuk et al, 2011;Feás et al, 2012).…”
Section: Composición De Las Flores Comestiblesunclassified